An Analysis of Discourse Markers in Donald Trump’s 2025 Rally Victory Speech - Faridatuz Zulfa; Evi Pebri Ila Rachma (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study is focused on the use of discourse markers in Donald Trmpu’s rally victory speech. The purposes of this study are to find out the types of discourse markers used during the speech and the functions by using Fraser’s theory (2009) to examine the types of discourse markers and Schiffrin’s theory (1987) to analyze their functions. In this study, the data used are words and phrases from the utterances uttered by Donald Trimp which included to discourse markers. Therefore, the researcher used qualitative research method to analyze this topic. The reearcher also used data analysis technique from Miles, Huberman, and Saldana (2014). In conclusion, the researcher found all types of discourse markers used by Donald Trump on his rally victory speech. There are 227 data included in the discourse markers. Among them are 54 contrastive discourse marker, 148 elaborative discourse markers, 20 inferential discourse markers, and 5 temporal discourse markers. Elaborative Discourse Markers are dominant used by Donald Trump. Based on the functions, the writer found that from 5 functions of discourse markers. There are Marker of Response, Marker of Connectives, Marker of Cause and Effect, and Marker of Information and Partiipation.